Treatment of blood blister-like aneurysms of the supraclinoid internal carotid artery using pipeline and lattice flow diverters and coiling - Xuan Chen; Zibo Zhou; Jinguang Gao; Jinlu Yu (Frontiers in Neurology)
BackgroundFlow diverters (FDs) have shown the potential to treat blood blister-like aneurysms (BBAs) of the supraclinoid internal carotid artery (ICA). We report a series of cases treated by both deploying FDs and coiling.MethodsBased on the Bojanowski classification, the BBAs of the supraclinoid ICA were classified into types I–IV. Based on the approach used for endovascular treatment (EVT) of the BBAs, the EVTs were categorized into types 1–3. The modified Rankin scale (mRS) was used to assess the clinical follow-up outcome.ResultsThirteen patients with 13 BBAs of the supraclinoid ICA who were aged 22–66 (49.8 ± 13.5) years were included. There were 12 females and 1 male. All patients had experienced subarachnoid hemorrhage. According to the Bojanowski’s et al. classification, a total of 2, 7, 3, and 1 BBAs were categorized as types I, II, III, and IV, respectively. Preoperative vasospasms were detected in 4 patients. EVT types 1, 2, and 3 were used to treat 4, 7, and 2 BBAs, respectively. After EVT, 2 patients with preoperative vasospasm experienced hemiparesis but later recovered. One patient with a preoperative vasospasm experienced multiple infarctions and died. One patient who discontinued antiplatelet therapy experienced multiple infarctions and suffered severe disability. ‌Twelve patients completed a post-EVT six-month follow-up, excluding the one with postoperative mortality.‌ The mRS scores were 0, 1, and 4 for 10, 1, and 1 patients, respectively. Eleven patients were subjected to angiographic follow-up. All BBAs were cured, and the supraclinoid ICAs were repaired.ConclusionFor patients with BBAs, deploying an FD and coiling can yield good outcomes. However, ischemic complications should not be overlooked.